Exploring curriculum approaches and issues: A descriptive analysis - Habiburrahim, Habiburrahim (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
A curriculum is a set of guidelines used to attain an educational goal, and it has at least four key elements: objective, material, method, and evaluation. The purpose of this descriptive study is to describe several curriculum approaches that are commonly employed in teaching and learning activities. Furthermore, this study discusses curriculum changes, the reasons that influence such changes, and the obstacles that each curriculum change presents. The study first elaborates on the disciplinary curriculum approach, emphasizing the idea of exploring a certain subject of science through single-focused lenses without integrating it into other connected sciences. Following an examination of the disciplinary curriculum approach, the study gives considerable information on multidisciplinary and interdisciplinary curriculum approaches that have the potential to improve students' critical thinking skills. This study concludes by delving into curriculum change as well as its motivating factors and challenges.